Frequency of enuresis and related factors among school children in Guilan province; a single center investigation - Afshin Safaei-Asl; Abtin Heydarzadeh; Alinaghi Karimi; Shohreh Maleknejad (Society of Diabetic Nephropathy Prevention, 2017)
Introduction: Enuresis is one of the most common diseases in children that has several physical and psychosocial effects on children and their parents. Enuresis is classified in primary and secondary groups which depends on various factors such as genetic predisposition, biological and developmental, psychological, social and economic factors. Objectives: This study aimed to determine the prevalence of enuresis in primary school-aged children and the role of related personal and family factors in Rasht. Patients and Methods: In this cross-sectional study, samples were randomly selected from Rasht's primary schools. Questionnaires were selected for each student and then completed by a health expert with invitation of a parent. Results: In this study, 1125 questionnaires were completed that 568 (50.5%) were boys and 557 (49.5%) were girls. The study showed that the prevalence of enuresis was 7.5% (n = 43) in boys and 4.1% (n = 23) in girls and overall is 5.9% (n = 66). The gender difference was statistically significant. There was statistically significant relation in two groups about personal factors such as history of urinary tract infections (UTIs), snoring, computer games and eating fast food and family factor such as family history of enuresis and the place of residence. Conclusion: The results showed that the prevalence of this disorder was lower than other studies, which it may be because of ethnic and cultural differences among the communities. Our results with enuresis prevalence and associated factors were comparable to other epidemiological studies from various countries.